EKSPLORASI BAHAN ALAMI SEBAGAI ALTERNATIF PENGGANTI BAHAN TAMBAHAN PANGAN (BTP) SINTETIK - W, Swastike; E, Suryanto; Rusman, Rusman; Jamhari, Jamhari; Jumeri, Jumeri (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2018)
This study aims to explore natural ingredients so that they can be used as alternatives to synthetic additives. The ingredients consist of red dragon fruit, red dragon fruit peel, carrots, beet root and purple sweet potatoes. The results showed that the best sources that have the potential as natural BTP (flavonoid content, antioxidant activity, vitamin C, and the natural color) were beet root carrots and purple sweet potatoes.